"Ain't Nobody Gone Take It from You!". Issue 2 (3rd March 2021) - Black, Fiona C.
Abstract : Dance, in both its historical formulations during the slave trade and its contemporary manifestations in carnival celebrations, has enormous significance for numerous Caribbean cultures. Using some biblical texts to think with (2 Sam 6: 14; Song 6: 13), this paper explores the historical and contemporary event of Junkanoo as a reflection of Bahamian culture and its interaction with colonialism and contemporary tourism. Junkanoo is not explicitly biblical or religious, though it does show the marks and tussles of colonization and hence Christianization. The biblical moments of movement and resistance considered here frame dance in various and interesting ways—as the vehicle for emotional expression, as liberation, as licensed revolt, as the tool of empire—allowing for exploration of dance as a multi-valent, political act, as much as a powerful reflection of affect.